Relationship Between Sociodemographic Backgrounds And Mothers’ Oral Health Knowledge, Attitude And Practice Of Their Preschool Children - Sayed Kamar, Syarifah Haizan; Jelani, Noor Inani; Mohamad Nor, Noraini (IIUM Medical Journal Malaysia, 2017)
Introduction: Mothers play important roles in their children’s oral health. The aim of this study is to determine the relationship between mothers’ sociodemographic backgrounds and their oral health knowledge, attitude and practice of their preschool children. Materials and Methods: A cross sectional study was conducted among 149 mothers of 4 to 6-year-old preschool children from selected kindergartens. Stratified cluster sampling was done to select kindergartens from urban and suburban areas in Kuantan, Pahang. Knowledge and attitude of mothers were assessed using selfadministered questionnaires and children’s oral health practice was recorded using three days tooth brushing diary. Data were analyzed using SPSS version 16.0. Results: Mothers had high oral health knowledge (Mean score 73.6%, SD 1.3%) and attitude (Mean score 73.2%, SD 2.4%) scores. Significant relationships were reported between mothers’ oral health knowledge and age (p=0.037), educational status (p0.05). Conclusion(s): Lack of further education, low household income and living further away from the city contributed to low oral health knowledge and poor oral health attitude among mothers, towards their preschool children. Younger mothers had lower oral health knowledge, whereas older mothers had poorer oral health attitude.